Do young Carollia perspicillata (Chiroptera: Phyllostomidae) present higher infestation rates of Streblidae (Diptera)? Jovens de Carollia perspicillata (Chiroptera: Phyllostomidae) apresentam maiores taxas de infestação de Streblidae (Diptera)? - CEL. Esbérard (Brazilian Journal of Biology, 2012)
Ecological aspects related to parasitism are one of the less studied issues in parasitology research, and the scarce evidence available supports that younger specimens present higher infestation rates. The purpose of this work is to establish if higher infestation rates are observed in nursing females and their young captured inside their roost. Bats were captured inside a shelter located in RPPN Estação Veracel, Santa Cruz de Cabrália, Bahia state, Brazil. A total of 56 individuals of Carollia perspicillata were observed, 17 captured inside the roost during the day and 39 in trails at night. Captures of C. perspicillata during the day in a shelter yielded similar infestation rates to bats netted in trails and higher prevalence. The hypothesis that young were more infected was confirmed, based on the higher infestation of nursing females with neonates and on the significant inverse relation between body weight and number of parasites in young and subadults. Aspectos ecológicos relacionados ao parasitismo são uma das questões menos estudadas em parasitologia e poucas evidências sobre indivíduos jovens apresentando maiores taxas de infestações estão disponíveis.O objetivo deste trabalho é estabelecer se a taxa de infestação mais elevada é observada em fêmeas lactantes e jovens capturados dentro de seu refúgio. Os morcegos foram capturados dentro de um abrigo localizado na RPPN EstaçãoVeracel, Santa Cruz deCabrália-Bahia, Brasil. Um total de 56 indivíduos de Carollia perspicillata foi observado, sendo que 17 indivíduos foram capturados dentro do refúgio, durante o dia, e 39 foram capturados em trilhas, à noite. Indivíduos de C. perspicillata capturados durante o dia no abrigo apresentaram índices de infestação semelhantes aos morcegos capturados em trilhas e maior prevalência. A hipótese de que jovens eram maisinfectados foi confirmada, com base na maior infestação de fêmeas com recém-nascidos e na relação inversa significativa entre o peso corporal e o número de parasitas em jovens e subadultos.